Productive Waqf-Based Educational Resource Management: A Case Study at As’adiyah Sengkang Islamic Boarding School - Wahyuni, Sri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Islamic schools must increase quality and financial independence because traditional finance limits sustainability. Waqf is a clever, sharia-compliant approach to making money. This study evaluates the As'adiyah Sengkang Islamic Boarding School's successful waqf-funded education. No study has evaluated an integrated Educational Resource Management (ERM) model for waqf profits allocation for curriculum development, educator welfare, and facility upkeep, despite As'adiyah Sengkang's success. Therefore, the purpose of this study is to comprehensively analyze and describe the ERM model based on the utilization of productive waqf proceeds, as well as to identify supporting and inhibiting factors for its implementation at As'adiyah Sengkang Islamic Boarding School. This study uses a qualitative approach with a descriptive case study. Data were collected through in-depth interviews with administrators (nazhir), Islamic boarding school leaders, and financial staff; direct observation of waqf assets and educational activities; and analysis of documents related to financial reports and resource allocation policies. The results of the study indicate that As'adiyah Sengkang applies a cyclical MSDP model, where the results of productive waqf investments are managed through a special business unit and allocated proportionally, with the main priority being improving teacher welfare (remuneration) and financing flagship programs. The contributions of this study are (1) Theoretical Contribution: Providing a theoretical model of sustainable Islamic MSDP based on endowment funds (productive waqf). (2) Practical Contribution: Providing best practices and applicable guidelines for other Islamic boarding schools in achieving financial independence and optimizing educational resources.